Is Proton Therapy a “Pro” for Breast Cancer? A Comparison of Proton vs. Non-proton Radiotherapy Using the National Cancer Database - Chowdhary, Mudit; Lee, Anna; Gao, Sarah; Wang, Dian; Barry, Parul N.; Diaz, Roberto; Bagadiya, Neeti R.; Park, Henry S.; Yu, James B.; Wilson, Lynn D.; Moran, Meena S.; Higgins, Susan A.; et al. (Frontiers in Oncology, 2019)
Background: There is limited data demonstrating the clinical benefit of proton radiotherapy (PRT) in breast cancer. Here we investigate the impact of PRT on overall survival (OS) and evaluate predictors associated with PRT use for patients with breast cancer in the National Cancer Database. Methods: Women with non-metastatic breast cancer treated with adjuvant radiotherapy from 2004-2014 were identified. Patients were stratified based on receipt of PRT or non-PRT (i.e. photons +/- electrons). A logistic regression model was used to determine predictors for PRT utilization. For OS, Multivariable analysis (MVA) was performed using Cox proportional hazard model. Results: A total of 724,492 women were identified: 871 received PRT and 723,621 received non-PRT. 58.3% of the PRT patients were group stage 0-1. Median follow-up time was 62.2 months. On multivariate logistic analysis, the following factors were found to be significant for receipt of PRT (all p<0.05): academic facility (odds ratio [OR]=2.50), South (OR=2.01) and West location (OR=12.43), left-sided (OR=1.21), ER-positive (OR=1.59), and mastectomy (OR=1.47); pT2-T4 disease predicted for decrease use (OR=0.79). PRT was not associated with OS on MVA for all patients: Hazard Ratio: 0.85, p=0.168. PRT remained not significant on MVA after stratifying for subsets likely associated with higher heart radiation doses, including: left-sided (p=0.140), inner-quadrant (p=0.173), mastectomy (p=0.095), node positivity (p=0.680), N2-N3 disease (p=0.880), and lymph node irradiation (LNI) (p=0.767). Conclusions: Receipt of PRT was associated with left-sided, ER+ tumors, mastectomy, South and West location, and academic facilities, but not higher group stages or LNI. PRT was not associated with OS, including in subsets likely at risk for higher heart doses. In light of the high cost of proton RT, these data question the utilization of PRT, especially in early stage patients with expected low heart doses, unless enrolled on a clinical trial.